2017
DOI: 10.1016/j.whi.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Access to Removal of Long-acting Reversible Contraceptive Methods Is an Essential Component of High-Quality Contraceptive Care

Abstract: Her interests include reproductive health, safety net services, and public financing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…Several women in our study reported that they did not want or choose immediate postpartum LARC because they did not like that they cannot remove the device themselves. Some women may encounter challenges to getting a LARC device removed when they desire, including resistance from providers and cost barriers [21]. Although Georgia Medicaid does not have any policies that may add barriers to LARC removal the way a few other states do [22], 41% of the women in our study were uninsured by the time of the interview.…”
Section: Discussionmentioning
confidence: 99%
“…Several women in our study reported that they did not want or choose immediate postpartum LARC because they did not like that they cannot remove the device themselves. Some women may encounter challenges to getting a LARC device removed when they desire, including resistance from providers and cost barriers [21]. Although Georgia Medicaid does not have any policies that may add barriers to LARC removal the way a few other states do [22], 41% of the women in our study were uninsured by the time of the interview.…”
Section: Discussionmentioning
confidence: 99%
“…Risks associated with insertion are low and similar to those at interval insertion, including perforation, infection, and vaginal bleeding . Although a higher risk of expulsion exists, this may be mitigated with access to built‐in or affordable removal or replacement services . Table includes elements of a targeted history for any woman considering an immediate postpartum IUD insertion to help explore her risk tolerance, abilities, and barriers.…”
Section: Shared Decision Making and Mitigating Coercionmentioning
confidence: 99%
“…A Cochrane review found that despite a higher rate of expulsion (20%‐27% of women expelled the device) for immediate postpartum insertion compared with 0% to 4.4% for interval insertion, continued long‐term use among those with postpartum insertion was similar to or greater than those women who had interval insertion . Rates of continued use are higher still when women have access to replacement or removal services beyond the postpartum period, which can correct for expelled or malpositioned devices …”
Section: Shared Decision Making and Mitigating Coercionmentioning
confidence: 99%
“…First, acknowledging that not all women desire a planned or well-timed pregnancy29 30 (or even, any pregnancy at all) is essential. Supporting women’s contraceptive decisions (to not use LARC, or requesting early removal, for example), is essential to providing high-quality contraceptive care31 and reproductive autonomy 32. Further, these findings contribute to the growing body of work that highlights the inadequacy of dichotomous conceptualisations of pregnancy as either intended or unintended in capturing women’s actual reproductive experiences (see for example30).…”
Section: Discussionmentioning
confidence: 89%